Theoretical analysis of the influence of band tail defects on PIN InGaN solar cells. Issue 5 (27th January 2016) - Wang, Baozhu; Feng, Yan; Meng, Lizhi; Wang, Min; Xiao, Hongling; Wang, Xiaoliang
Abstract: InGaN solar cells have higher conversion efficiency than traditional Si based solar cells. However, efficiency of experimental InGaN solar cell is lower than expected. There are still several problems, such as the structure design of InGaN solar cells, the quality of InGaN materials, need to be discussed and solved. Thus, the researches of structure design and defect effects are important for the implications of InGaN solar cells. The performance of p‐GaN/i‐In x Ga1– x /n‐GaN solar cells with different In content is simulated by AMPS‐1D. It is found that the optimum efficiency of p‐GaN/i‐In x Ga1– x N/n‐GaN solar cells is 8.9% when the In content is 0.26. The p‐GaN/i‐In0.26 Ga0.74 /n‐GaN solar cells with band tail defects are simulated. The simulated results show the efficiency decreases with the increase of the E‐character. And the efficiency decreases sharply from 8.30% to 7.19% when the capture cross section is 10 –14 cm –2 . (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)